Enzymatic Production Of Sago Starch Oligosaccharides And Their Fermentation By Lactobacillus SPP - Rashid, Rinani Shima Abd. (2011)
The potential of sago starch short chain oligosaccharides (SCO) to enhance the growth of Lactobacillus spp. was studied. Partially gelatinized sago starch was hydrolyzed at pH 6.2 for 48 hours at various temperatures (45 °C - 75 °C) and concentrations (1% - 6% (v/w)) of α-amylase (Termamyl 120L). Sago starch hydrolysis using 2% (v/w) α-amylase, at 65 °C yielded a total SCO of 14.6 g/kg, while enzymatic hydrolysis at 75 °C with 1% (v/w) α-amylase produced the highest concentration of SCO reaching 15.0 g/kg after 48 hours hydrolysis.